Integrasi Tanggung Jawab Sosial Perusahaan (CSR) dan Etika dalam Formulasi dan Implementasi Strategi: Pilar Keberlanjutan dan Keunggulan Kompetitif - Noval Nur; Alman; Fardiansyah (Indo Publishing, 2025)
This study examines the paradigm shift from the traditional view of Corporate Social Responsibility (CSR) and Ethics as cost centers to the modern view of them as strategic assets that create shared value (CSV). The primary objective of this study is to analyze how companies integrate ethical and CSR dimensions into the entire strategic management process, from formulation to implementation, and to identify their impact on sustainability and long-term competitive advantage.Through a qualitative-descriptive approach (based on an extensive literature review and case study analysis), the findings indicate that effective integration requires aligning ethical values with the company's Vision and Mission, as well as applying Carroll's Pyramid Framework as a basis for strategy formulation. The study concludes that companies that successfully internalize ethics and CSR into their core strategies are able to simultaneously achieve the